ANALISIS KINERJA SIMPANG BERSINYAL: Studi Kasus: Persimpangan Jl. Raya Nginden – Jl. Raya Prapen – Jl. Panjang Jiwo - Jl. Jagir Wonokromo - Syahril Wahyu Saifuddin; Hary Moetriono (LPPM Universitas Bina Bangsa, 2023)
It is the capital of East Java Province. Surabaya is the second largest city in Indonesia after Jakarta. Based on data from the Surabaya City Statistics Center in 2020, the population of Surabaya City is 2,904,751 people. Congestion is one of the problems that occur in cities including the city of Surabaya, the occurrence of congestion due to the accumulation of vehicle volume at certain hours so that it accumulates vehicles which causes a halt in traffic flow at a highway intersection. One of them is the intersection of Jalan Raya Nginden - Jalan Raya Prapen - Jalan Panjang Jiwo - Jalan Jagir Wonokromo.The method used in this study is the Indonesian Road Capacity Manual method in 1997 (MKJI 1997). The author conducted a traffic survey by calculating the number of vehicles passing for 3 days, namely Tuesday, Wednesday and Thursday during rush hour, namely in the morning at 06.00 – 09.00 WIB, during the day 11.00 – 14.00 WIB and in the afternoon 15.00 – 18.00 WIB. The calculation is carried out per 15 minutes. And itcan be calculated the amount of traffic volume, the capacity of intersections and the magnitude of the degree of saturation, The results showed that the maximum traffic volume at the existing condition of the intersection of Jalan Raya Nginden - Jalan Raya Prapen - Jalan Panjang Jiwo - Jalan Jagir Wonokromo occurred on Wednesday at 15.00 – 18.00 WIB. Jalan Raya Nginden amounted to 1610 smp / hour, Jalan Raya Prapen 1761 smp / hour, Jalan Panjang Jiwo amounted to 1540 smp / hour, Jalan Jagir Wonokromo amounted to 1680 smp / hour. The result of the degree of saturation at each intersection is 0.90